The advent of modern economics in Portugal - Bastien, Carlos (2009)
As far as economic theory is concerned Portugal has never had a strong tradition or originality. As a semi-peripherial society it has been a late receiver of innovations come out from the main producer centres of economic ideas, often in a partial, ill digested way, adapting them to the local conditions. The post World War II years would be a crutial period in that process of import and adaptation. Then, the ruling classes became particularly aware of Portugal's economic backwardness and a strategy to achieve economic growth and modernization was implemented, while an inevitable larger integration in the world economy and cultural life took place. Such an enviroment demanded a larger concern with economic issues and theories, weaken the position of corporative economics, which had been dominant since the 1930's, and allowed a sudden introduction of modern economic theories, namely neoclassical, keynesian, and marxist economics, by then almost unknown. A significant reform of economic teaching, the advent of research institutions and reviews on the subject were decisive to spread the new theories.